Poloxamer-enhanced solubility of griseofulvin and its related antifungal activity against Trichophyton spp. - Vanessa Pittol; Kleyton Santos Veras; Samuel Kaiser; Letícia Jacobi Danielli; Alexandre Meneghello Fuentefria; George González Ortega (Universidade de São Paulo, 2022)
Abstract Poorly water-soluble drugs, such as the antifungal drug griseofulvin (GF), exhibit limited bioavailability, despite their high membrane permeability. Several technological approaches have been proposed to enhance the water solubility and bioavailability of GF, including micellar solubilization. Poloxamers are amphiphilic block copolymers that increase drug solubility by forming micelles and supra-micellar structures via molecular self-association. In this regard, the aim of this study was to evaluate the water solubility increment of GF by poloxamer 407 (P407) and its effect on the antifungal activity against three Trichophyton mentagrophytes and two T. rubrum isolates. The GF water solubility profile with P407 revealed a non-linear behavior, well-fitted by the sigmoid model of Morgan-Mercer-Flodin. The polymer promoted an 8-fold increase in GF water solubility. Fourier-transform infrared (FT-IR) spectroscopy, differential scanning calorimetry (DSC), and 2D nuclear magnetic resonance (NMR Roesy) spectroscopy suggested a GF-P407 interaction, which occurs in the GF cyclohexene ring. These results were supported by an increase in the water solubility of the GF impurities with the same molecular structure. The MIC values recorded for GF ranged from 0.0028 to 0.0172 mM, except for T. Mentagrophytes TME34. Notably, the micellar solubilization of GF did not increase its antifungal activity, which could be related to the high binding constant between GF and P407.